'Regions of unthought' – the danger and the freedom of film archiving and (trans) national film heritage in the Balkans. Issue 2 (3rd May 2020) - Grgić, Ana
Abstract: The 'Balkan imaginary space' and its characteristics – fragmentation, fluidity, and flexible contours, not only apply to scholarly perspectives (Todorova, Iordanova, Bakić-Hayden, Glenny, Goldsworthy, Kaser) and hegemonic understanding of the geopolitical designations of the region, but could also be true of national film archives and national film historiography. Taking Maria Todorova's cue of being 'in and beyond the West', and looking toward 'regions of unthought' ([1997] 2009), this paper aims to provide a fresh perspective on the discursive meanings and unique positioning of national film archives and heritage in the Balkans, and how these contribute to the shaping of a (trans) national film historiography. When observing the trajectories of filmmakers and cinema exhibition and distribution activities across the Balkan region, and in particular, the cinematographer and film entrepreneur Louis Pitrolf de Beéry, and the 'Balkan cinema pioneers', the brothers Ienache and Milton Manakia, allows for the emergence of the cosmopolitan and transnational character of early cinema. Consequently, due to the mutation of borders, the dissolution of empires and the fragmentation of previously constituted federal nations, the notion of 'national' itself becomes complex and not easily discernible, leading to questions of who keeps the memory, where memory is kept and for whom. Ultimately, this leads to the necessity to reconsider the development of early cinema in the countries of the Balkan region through an increasingly transnational and perhaps global framework.